(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Complicated fractures of bones can be difficult to treat, and there is a high probability that further operative corrections need to be carried out. In the present work, we present a case study, where a model of the humerus of a six-year-old male patient was 3D-printed from a segmented CT-dataset for a preoperative optimization of the geometric parameters of a supracondylar domosteotomy. The experimental simulation of the treatment has proven very useful to the physician, and the patient has been treated successfully.